THE ROLE OF THE FIRST LANGUAGE IN MANDARIN LANGUAGE ACQUISITION: AN INTERLANGUAGE STUDY OF MULTILINGUAL UNIVERSITY STUDENTS - Nasywa, Nabilah Ramadhina; Choirot, Elok Umdhatul; Paramesti, Andhini Rajwa; Atmaja Widodo, Harits Tri; Maria Mintowati; Rokhisotul Amaliyah (Lingue : Jurnal Bahasa, Budaya, dan Sastra, 2026)
This study aims to analyze the role of the first language in the Mandarin language acquisition process of 2024 cohort students in the Mandarin Language Education Study Program at the State University of Surabaya. The main problem in the study is the students' difficulties in aspects of pronunciation (phonology), tone system (tonology), and grammar (syntax) of the Mandarin language, which are influenced by their first language. The research method used is a descriptive quantitative approach with data collection techniques through questionnaires to 80 respondents who have diverse first-language backgrounds (Indonesian, local language, and English). The results show that the first language is highly influential and serves as the primary source of interference for students, particularly in phonology; difficulties were found in pronouncing sounds such as "zh," "ch," "sh," "r," and "ü," which do not exist in the first language. In tones, respondents faced challenges in distinguishing tones 1 to 4 due to the absence of a tonal system in their first language. In grammar, a tendency toward direct translation was identified, which triggers sentence structure errors. In addition to linguistic factors, external factors such as the learning environment, lack of practice, and dependence on pinyin also affect the process of mastering the target language. Overall, this study concludes that the first language plays a significant role both as a source of interference and as a supporting factor in Mandarin language acquisition